A clinical and radiographic comparison of platelet-rich fibrin and lyophilized platelet-derived preparation as pulpotomy agent in primary molars - V Devi Praja; Anil L Muttath; Vinola Duraisamy; Nandhini B Selvarajan; V Suresh Kumar; John Baby John (Wolters Kluwer Medknow Publications, 2020)
Introduction: Vital pulpotomy in primary molar teeth is aimed to retain the tooth in function until it is replaced by its successors. Aim: The aim of this study was to evaluate and compare platelet-rich fibrin (PRF) and lyophilized platelet-derived preparation (LPDP) as a pulpotomy agent in primary molars. Materials and Methods: Forty primary molars from 20 healthy children aged 5-9 years requiring pulpotomy in the contralateral side of mandible were randomly selected. In both the groups, pulpotomy was carried out by removing coronal pulp and achieving hemostasis, the radicular part of pulp tissue was packed with PRF preparation in Group I and LPDP (Mothercell Research Centre, Trichy, Tamil Nadu, India) in Group II. The teeth were restored with zinc oxide eugenol and glass ionomer cement (GIC), followed by stainless steel crown in the same visit. Clinical and radiographic evaluation was undertaken at 1, 3, and 6 months interval. Results: The overall success rate was 90% in PRF group and 95% in LPDP group at the end of 6 months. The results were statistically nonsignificant between the groups (P > 0.05). Conclusion: The overall outcome of the study suggests that PRF and LPDP are acceptable pulpotomy agents and are promising in the era of new vital pulp therapy procedure.